Strategies To Increase Organizational Citizenship Behavior Through Strengthening Organizational Culture, Transformational Leadership, Self-Efficacy, And Trust - Nisa, Afiatin; Setyaningsih, Sri; Suhendra, Suhendra (Kontigensi : Jurnal Ilmiah Manajemen, 2025)
This study aims to explore strategies for improving Organizational Citizenship Behavior (OCB) among teachers, particularly focusing on the roles of organizational culture, transformational leadership, self-efficacy, and trust in enhancing teachers' voluntary behavior within educational organizations. Using quantitative research methods with path analysis and SITOREM analysis, the research examines the direct and indirect effects of these variables on OCB. The results indicate that organizational culture, transformational leadership, self-efficacy, and trust all have direct positive and significant effects on OCB. Furthermore, trust serves as an effective intervening variable in the relationship between organizational culture, transformational leadership, self-efficacy, and OCB. The findings suggest that enhancing these key factors can significantly improve teachers' OCB, leading to a more productive, effective, and supportive educational environment. The SITOREM analysis provides insights into the priority indicators that need to be developed to optimize the strategies for fostering OCB in educational settings.